An energy-saving glasshouse film reduces seasonal, and cultivar dependent Capsicum yield due to light limited photosynthesis - Sachin G. Chavan; Xin He; Chelsea Maier; Yagiz Alagoz; Sidra Anwar; Zhong-Hua Chen; Oula Ghannoum; Christopher I. Cazzonelli; David T. Tissue (Annals of Agricultural Sciences, 2023)
Glasshouse films can be used to reduce energy costs by limiting non-productive heat-generating radiation, but the impact on yield of greenhouse horticultural crops remains unknown. The effects of energy-saving film ULR-80 (ultra-low-reflectivity film with 80 % light transmission referred to as Smart Glass; SG) designed to block long wavelength light that generates heat also reduced photosynthetically active radiation (PAR) consequently affecting crop morphology, photosynthesis, leaf pigments, and yield of two hydroponically grown capsicum (Capsicum annuum L.) cultivars (Red and Orange). The crops were grown in four high-tech glasshouse bays over two seasons of similar daily light integrals (DLI) during ascending [Autumn Experiment (AE)] and descending [Summer Experiment (SE)] photoperiods. The Red cultivar exhibited higher photosynthetic rates (light saturated - Asat) and yield than the Orange cultivar in control glass but displayed stronger reductions in modelled photosynthetic rates at growth light and yield in SG without changes in photosynthetic capacity. Foliar pigment ratios of chlorophyll a/b and carotenoid:chlorophyll remained unaffected by the SG during both seasons indicating that chloroplast homeostasis was similar between SG and control. The seasonal differences in photosynthetic pigments and xanthophyll de-epoxidation state (DPS) revealed that cultivars were able to sense the SG-altered light environment during the AE, but not SE. The SE correlated with a lower daily light level and a substantial yield reduction of 29 % and 13 % in Red and Orange cultivars, respectively. Thus, SG-induced higher reductions in yield during the SE indicate that SG may be more beneficial for capsicum crops planted during AE.